Single-chip pressure sensor radiation hardness research - Artamonov, A.S.; Boychenko, D.V.; Nikiforov, A.Y.; Sogoyan, A.V.; Shelepin, N.A.; Telets, V.A.; Tverskoy, M.G. (2001 6th European Conference on Radiation and Its Effects on Components and Systems, 2001)
Transient and steady-state radiation response of a single-chip pressure sensor is investigated in (1...6) atm pressure range. The independence of radiation behavior on the applied pressure was observed. The sensor sensitivity variation is less than 0.01 % for total dose up to 3 Mrd. A model for dose rate effects is developed.